DUAL ROLE CONFLICT WITH BURNOUT SYNDROME IN NURSES - Ryandini, Tiara Putri; Mokhamad Nurhadi; Mei Widyawati (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Burnout syndrome in nurses who are too busy tall can influence ability individual in face environment work , so that arise various consequence Good both mentally and physically physical which can seriously disrupt the service process . Research This aiming For know connection conflict role double with burnout syndrome in nurses at RSNU Tuban . Research This is non- experimental research with design analytic correlational and the approach used is cross sectional . Respondents in study This totaling 40 respondents with use total sampling technique . Variables free is conflict role double and variable tied up is burnout syndrome. The instrument used is questionnaire . Research results show conflict role double burden and burnout syndrome in nurses at RSNU Tuban is in the category moderate . The statistical test used is the Spearman rho test with α = 0.05 and obtained value of ρ = ​​0.000 (ρ = <0.05) then H1 is accepted . Research conclusion This is there is significant relationship​ between conflict role double with burnout syndrome in nurses at RSNU Tuban . Therefore that , the more tall conflict role double so the more the level of burnout syndrome is also high .